Experimental and kinetic modeling studies of furan pyrolysis: Fuel decomposition and aromatic ring formation. (15th October 2017) - Cheng, Zhanjun; Tan, Yaoyao; Wei, Lixia; Xing, Lili; Yang, Jiuzhong; Zhang, Lidong; Guan, Yanan; Yan, Beibei; Chen, Guanyi; Leung, Dennis Y.C.
Highlights: The pyrolysis of furan was studied using SVUV-PIMS in a flow reactor at 30 Torr. C3 H3 is suggested to be mainly formed from propyne instead of directly from furan. C3 H3 and C6 H5 are the most important precursors of large aromatic species. Abstract: The pyrolysis of furan was studied from 1100 to 1600 K in a flow reactor at low pressure (30 Torr). Synchrotron vacuum ultraviolet photoionization mass spectrometry (SVUV-PIMS) was used for isomeric identification and mole fraction measurements of the pyrolysis products, especially the free radicals. Specific products were observed and measured for the unimolecular decomposition reactions of furan, such as propyne + CO, acetylene + ketene and propargyl radical, etc. An updated combustion model of furan from Somers model was adopted to simulate the mole fraction profiles of the pyrolysis species measured in this work. Kinetic modeling analysis indicated that the decomposition of furan is mainly controlled by the unimolecular decomposition reactions under the investigated conditions. Based on the experimental results and theoretical simulations, propargyl radical is suggested to be mainly formed from the direct unimolecular decomposition of propyne instead of that of furan. In furan pyrolysis, propargyl and phenyl radicals are the most important precursors of large aromatic species.